International Experience with Open Access to Power Grids : Synthesis Report - World Bank (Washington, DC, 2014)
Reliable and affordable supply of electricity is a key driver of economic growth. In recent decades, many developing and emerging economies have embarked on efforts to enhance the efficiency of their electricity markets. The quest for efficiency often involves structural reforms such as unbundling and other measures designed to support greater competition in the power sector. Open Access (OA) to Transmission and Distribution (T&D) grids by market participants is an essential element in this reform process. The study has proceeded on two tracks: one based on empirical findings from specific country cases, and a generic one synthesizing the emerging global issues in OA. Reports for the country studies have been prepared for Brazil, Peru, Turkey, India, and the Philippines. In addition, a global review of the experience in a broader group of countries, both developed and developing, has been undertaken. Overall, the study has taken a broad approach to defining OA - going well beyond the minimalist notion of simply guaranteeing legal access to the grid for generators and wholesale buyers.